2015
DOI: 10.1111/cei.12638
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress causes autophagy and apoptosis leading to cellular redistribution of the autoantigens Ro/Sjögren's syndrome-related antigen A (SSA) and La/SSB in salivary gland epithelial cells

Abstract: SummaryThe aim of this study was to examine the levels of endoplasmic reticulum (ER) stress in minor salivary glands, to investigate the interplay between ER stress-induced autophagy and apoptosis in human salivary gland (HSG) cells and to test the effect of ER stress-induced apoptosis on the cellular redistribution of the two major Sj€ ogren's syndrome (SS) autoantigens Ro/ Sj€ ogren's syndrome-related antigen A (SSA) and La/Sj€ ogren's syndromerelated antigen B (SSB). Minor salivary gland biopsies from SS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…In our model, we found ANXA2 and ENO3 in the membrane fraction of the cell in the fracture group only, which could make it more accessible to various immunoglobulins. In Sjogrens syndrome, for example, major epithelial autoantigens display cellular re-distribution into the cell membrane, therefore making them more available to auto-antibodies (Katsiougiannis et al, 2015). Re-localization of autoantigens can even occur extracellularly; The nuclear DNA sensor IFI16, elevated in various autoimmune conditions, has been shown to re-localize from the nucleus to the extracellular milieu (Sporn and Vilcek, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In our model, we found ANXA2 and ENO3 in the membrane fraction of the cell in the fracture group only, which could make it more accessible to various immunoglobulins. In Sjogrens syndrome, for example, major epithelial autoantigens display cellular re-distribution into the cell membrane, therefore making them more available to auto-antibodies (Katsiougiannis et al, 2015). Re-localization of autoantigens can even occur extracellularly; The nuclear DNA sensor IFI16, elevated in various autoimmune conditions, has been shown to re-localize from the nucleus to the extracellular milieu (Sporn and Vilcek, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ER stress is activated in minor salivary gland epithelial cells from Sjögren's syndrome (SS) patients. Moreover, an interplay between ER stress‐induced autophagy and apoptosis has also been suggested with regard to SS autoantigens Ro/SSA and La/SSB . The ER is an important intracellular organelle that is not only important for regulating Ca 2+ homeostasis but is also essential for the synthesis and folding of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a study from our group demonstrated that induction of apoptosis in HSG cells after triggering of ER stress with TG, showed that autoantigens Ro and La were detected in the apoptotic blebs of these cells . In addition, IL‐6 mRNA was one of the cytokines that was detected in ductal and acinar cells in salivary gland biopsies from SS patients as well as IRF1 mRNA was upregulated in the epithelial cells of SS patients .…”
Section: Er Stress Autophagy Apoptosis and Immune Reactionmentioning
confidence: 93%